A Different Beast? Televised Election Debates in Parliamentary Democracies. (October 2016) - Anstead, Nick
Research on televised election debates has been dominated by studies of the United States. As a result, we know far less about other national contexts, including many parliamentary democracies that now hold televised election debates. This article makes two contributions to address this. Theoretically, the study argues that traditional approaches for understanding the development of campaign communication practices (particularly, Americanization and hybridization) are limiting when applied to television debates and instead offers an alternative theoretical approach, the concept of speciation drawn from biological science. This is then applied in the empirical section of the article in a comparative analysis of the evolution of televised election debates in four parliamentary democracies: Australia, Canada, West Germany/Germany, and the United Kingdom. Based on this analysis, the article argues that the logic of parliamentary democracy coupled with more diffuse party systems has created a distinctive type of televised debate, generally more open to smaller parties based on their success at winning seats in the legislature.